FEATURES OF DESIGNING A MODERN OFFICE SPACE, ITS EQUIPMENT AND FURNITURE - Ahliullin , R. M.; Bulhakova, T. V.; Skliarenko, N. V.; Ostapyk , S. V.; Iskimzhi, A. A. (Art and Design, 2023)
The aim of the study is to identify the main factors, modern approaches and methods of creating a comfortable office space based on the analysis of modern domestic and foreign experience in designing this type of premises. Methodology. Critical analysis of scientific sources on the research topic, normative and reference literature, comparative analysis of advanced domestic and foreign experience in office interior design, and a synthesis of the research results have been used in the study. Results. Historical aspects of the development of offices and modern trends in the interior design of this type of premises are considered. The main factors of creating a comfortable office space are identified: design in accordance with modern ergonomic requirements; implementation of aesthetic principles of interior design, effective functional and planning organisation. The ergonomic criteria for workplace organisation are presented, and the main aspects of office ergonomics are highlighted. Based on the analysis of modern design experience, approaches and techniques of artistic and aesthetic, functional and planning solutions for office spaces are identified. In particular, rational planning that combines common communication spaces with individual workstations, artistic and aesthetic solutions with balanced colour palette and accents, optimal lighting and modern ergonomic equipment are becoming integral components of an effective modern office space. The scientific novelty lies in determining the main factors in creating a comfortable office space based on the analysis of modern interior design practice for this type of premises, identifying current trends, approaches and techniques for creating the office interior, which is a further contribution to the development of research on office environment design. The practical significance of the results obtained lies in the possibility of their application by designers and employers when designing office interiors.